Presentation and Real-World Management of Giant Cell Arteritis (Artemis Study) - Mahr, Alfred; Hachulla, Eric; de Boysson, Hubert; Guerroui, Nassim; Héron, Emmanuel; Vinzio, Stéphane; Broner, Jonathan; Lapébie, François-Xavier; Michaud, Martin; Sailler, Laurent; Zenone, Thierry; Djerad, Mohamed; et al. (Frontiers in Medicine, 2021)
Background: Few studies of daily practice for patients with giant cell arteritis (GCA) are available. This French study aimed to describe the characteristics and management of GCA in a real-life setting. Methods: Cross-sectional, non-interventional, multicenter study of patients ≥50 years old who consulted hospital-based specialists for GCA and were under treatment. Patient characteristics and journey, diagnostic methods and treatments were collected. Descriptive analyses were performed. Results: In total, 306 patients (67% females, mean age 74 ± 8 years old) were recruited by 69 physicians (internists: 85%, rheumatologists: 15%); 13% of patients had newly diagnosed GCA (diagnosis-to-visit interval <6 weeks). Overall median disease duration was 13 months (interquartile range 5–26). Most patients were referred by general practitioners (56%), then ophthalmologists (10%) and neurologists (7%). Most common comorbidities were hypertension (46%), psychiatric disorders (10%), dyslipidemia (12%), diabetes (9%), and osteoporosis (6%). Initial GCA presentations included cranial symptoms (89%), constitutional symptoms (74%), polymyalgia rheumatica (48%), and/or other extra-cranial manifestations (35%). Overall, 85, 31, 26, and 30% of patients underwent temporal artery biopsy, high-resolution temporal artery Doppler ultrasonography, 18FDG-PET, and aortic angio-CT, respectively. All patients received glucocorticoids, which were ongoing for 89%; 29% also received adjunct medication(s) (methotrexate: 19%, tocilizumab: 15%). A total of 40% had relapse(s); the median time to the first relapse was 10 months. Also, 37% had comorbidity(ies) related to or aggravated by glucocorticoids therapy. Conclusion: This large observational study provides insight into current medical practices for GCA. More than one third of patients had comorbidities related to glucocorticoid therapy for a median disease duration of 13 months. Methotrexate and tocilizumab were the most common adjunct medications.